A new energy regeneration system for A BLDC motor driven electric vehicle - R. Palanisamy; Rohit Sahasrabuddhe; Mathur Kartik Hiteshkumar; Jay Anil Puranik (Institute of Advanced Engineering and Science, 2021)
Amidst the ever-increasing advancements in the technological realm-the electrical vehicle industry too has seen several leaps. This particularly owes to three primary factors one, the fact that we are running out of conventional resources like petrol and diesel; two, higher efficiency of electric vehicles; and finally, less pollution caused by them. This has led to a burgeoning in the use of BLDC motors with electronic commutation not only in EVs but also in industrial and commercial applications. This requires an enhanced driving and control mechanism to tap the efficiency that such motors provide to increase performance and to get better controllability and reliability. This paper presents a controller for this EV motor driver with increased efficiency by combining various strategies.